Comparative study of the heating surface impact on porous-material-involved spray system for electronic cooling – an experimental approach. (5th May 2018) - Wang, Ji-Xiang; Li, Yun-Ze; Mao, Yu-Feng; Li, En-Hui; Ning, Xianwen; Ji, Xin-Yan
Graphical abstract: Highlights: A space-oriented spray system integrated with porous material is the study focus. Impacts of three heating surface types were investigated by comparative study. A maximum cooling enhancement of 125.3% was observed in the comparative study. Best heating surface type was selected considering performance and space application. Correlations were obtained by dimensionless study to gain an accurate prediction. Abstract: A spray cooling system integrated with porous material was previously studied with an emphasis on the space-oriented application. As an extension, this paper presents a comparative study of cooling performances of three target surface processing methods (S1, S2 and S3). Among them S1 is a normal naked flat surface which functions as a reference. The latter two adopt phase-change microfluidic cooling tactics using porous foamed copper (PFC) which can realize liquid loop control and vapour-liquid separation in various gravitational field due to favourable characteristics possessed by porous meteal materials such as the capillary force and superhydrophilicity. Different from our previous study which centres on S3, the present one also includes thermal tests on S1 and S2. Results of the experiment and related comparative studies of the three surface processing methods are presented as well where effects of mass flow rate and spray distance upon heat transfer characteristics on the cooling performance are disclosed. Conclusions can be drawn that the S2 has the best cooling performance since the maximum heat flux can reach 470.9 W/cm 2 under the given operation condition. An enhancement of 125.3% in terms of the maximum heat flux is attained compared with that for the S3 and 24.58% for the S1. The comparative study illustrates that the S2 is a relatively efficient form in cooling performance which retains properties that a space-oriented system should possess while eliminates the shortcomings such as reduced droplet impingement and huge thermal resistance when a layer of PFC is applied as well. In addition, empirical correlations based on experimental results for S2 and S3 are developed under the dimensionless study for the performance prediction with the relative errors of only ±1.84% and ±1.50% respectively.